(untitled) (Foro de Educacion, 2016)
The present theoretical study provides an overview of the somewhat hectic changes in Hungarian public education and, relatedly, teacher training in the past two and a half decades. The dynamic of harmony and disharmony that these changes are characterised by has created a rather quaint situation in educational policies. As a result, the trends that prevail in the Hungarian education system are some of the most distinctively atypical ones in the whole of Europe today, while higher education, including teacher training, is undergoing significant functional changes, which are relatively new in the international context as well.